Esterification of free fatty acids in simulated cooking oil using sulphuric acids as catalyst: - pre-treatment of feedstock for biodiesel production - Mohd Aqiel, Mohd Hashim (2014)
The objective of this research is to study the batch kinetic of FFAs effect of esterification by evaluating the parameters over a wide range operation conditions those are, effect of catalyst loading and methanol to oil feed molar ratio and time effect. The scope of the research is focus on limited to raw material of the simulated cooking oil by changing the parameters such as catalyst loading, methanol to oil molar ratio and time effect. Study will be focusing only for pre-treatment process. In this paper raw material (virgin oil) is to be simulated with free fatty acids to study the batch kinetic of FFAs effect of esterification by evaluating the parameters over a wide range operating conditions those are elimination of mass transfer resistance, effect of catalyst loading, methanol to oil feed molar ratio and time effect. The Gas Chromatography (GC) equipped with HP-5 silica capillary column will be used in this research also with the titration technique to get the FFA reading. The research uses sulphuric acid as the catalyst. With proper research focus and development, waste cooking oil can indeed become the next ideal feedstock for biodiesel